Appealing to the crowd: ethical justifications in Canadian medical crowdfunding campaigns. Issue 6 (30th January 2017) - Snyder, Jeremy; Crooks, Valorie A; Mathers, Annalise; Chow-White, Peter
Abstract : Medical crowdfunding is growing in terms of the number of active campaigns, amount of funding raised and public visibility. Little is known about how campaigners appeal to potential donors outside of anecdotal evidence collected in news reports on specific medical crowdfunding campaigns. This paper offers a first step towards addressing this knowledge gap by examining medical crowdfunding campaigns for Canadian recipients. Using 80 medical crowdfunding campaigns for Canadian recipients, we analyse how Canadians justify to others that they ought to contribute to funding their health needs. We find the justifications campaigners tend to fall into three themes: personal connections, depth of need and giving back. We further discuss how these appeals can understood in terms of ethical justifications for giving and how these justifications should be assessed in light of the academic literature on ethical concerns raised by medical crowdfunding.